Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1570-7458.2000.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Odour sensitivity of antennal olfactory cells underlying grooved pegs of Anopheles gambiae s.s. and An. quadriannulatus

Abstract: In female mosquitoes of the anthropophilic species Anopheles gambiae Giles s.s. and the zoophilic An. quadriannulatus Theobald single sensillum recordings from grooved pegs were made. In both species, the majority of these sensilla responded to ammonium hydroxide, butylamine and propanoic acid, whereas a smaller part responded to acetone. Lactic acid, butanone, 3‐methyl phenol and 1‐octen‐3‐ol evoked responses in a minority of grooved pegs only. In An. gambiae these four substances evoked either excitatory or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Recent studies with An. gambiae s.s. have confirmed that more than half the grooved pegs on the antennae increase their firing rate in the presence of water vapour and that some respond to low humidity, suggesting that these receptors play a role in humidity perception [28]. Whilst it has been shown that humidity is important for the survival of mosquitoes [29], a clear difference in the behaviour of unfed and gravid females was demonstrated in the presented WHO tube experiments.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies with An. gambiae s.s. have confirmed that more than half the grooved pegs on the antennae increase their firing rate in the presence of water vapour and that some respond to low humidity, suggesting that these receptors play a role in humidity perception [28]. Whilst it has been shown that humidity is important for the survival of mosquitoes [29], a clear difference in the behaviour of unfed and gravid females was demonstrated in the presented WHO tube experiments.…”
Section: Discussionmentioning
confidence: 61%
“…2d, e, Additional file 10: Figure S4, Additional file 11: Figure S5A). Interestingly, 1-octen-3-ol, a known mosquito adult attractant produced by microbes [43], displayed the greatest calcium response, followed by butylamine and ethyl acetate, with the former previously documented to induce a response in activated grooved-peg OSNs in Anopheles gambiae , Anopheles quadriannulatus , and Culex quinquefasciatus [27, 44]. Moreover, when observing muscle responses to the same stimuli we observed significant calcium increases in 5 of the 6 stimuli that also displayed significant responses in the DE.…”
Section: Resultsmentioning
confidence: 99%
“…quadriannulatus and An. atroparvus (Van Thiel) (Broek and Otter, 1999;Broek and Otter, 2000). At the peripheral level, no major differences in responses to several host volatiles were observed between these mosquito species with known differences in zoophilic and anthropophilic feeding preferences.…”
Section: Physiology Of Olfactory Behaviormentioning
confidence: 99%